Direct organogenesis in single bud explant of lasoda (Cordia myxa Roxb.) (Indian Journal of Arid Horticulture, 2025)
Organogenesis of shoot and root in single bud explant taken from mature tree of Lasoda (Cordia myxa Roxb) has been achieved. Organogenesis was obtained by placing nodal explant on shoot induction medium and subsequently on rooting medium. More than 90% culture were responsive for in-vitro axillary shoot proliferation on MS media supplemented with BA 2.0 mg and NAA 0.1 mg per litre. After culture period of 6-8 week, the nodal explants with microshoot were rooted on the MS media supplemented with 3g activated charcoal and different level of NAA (0, 1, 3 and 6 mg/litre). The season and position of explant on the mother plant was also shown to influence in-vitro performance of the regeneration in terms of establishment of aseptic culture, percentage of responsive explants and intensity of leaching of growth inhibitory phenolics.
Keywords: Cordia myxa; tissue culture; organogenesis